SOCIO-ECONOMIC FACTORS RELATED TO REARING FEMALE DOGS IN INDIA: RELATION TO THE DEVELOPMENT OF CEH-PYOMETRA - PATRA, M K; SINGH, U K; K S, JISNA; T R, RAJIN; DE, U K; SAXENA, A C; KRISHNASWAMY, NARAYANAN; KUMAR, H (The Indian Journal of Animal Reproduction, 2021)
Pyometra is one of the major reproductive problems in intact bitches at middle to advance age. Present studydescribes the impact of breed, age, management and breeding practices of dog in the prevalence of CEH-pyometrain the bitch. A questionnaire based questionnaire based interview was conducted on 93 pet owners who have visitedthe Gynaecology unit of Referral Veterinary Polyclinic, Indian Veterinary Research Institute, Izatnagar. The pointprevalence of pyometra was 34.4%. About 76.3% responders mentioned the purpose of keeping pets as a part ofhobby or special interest to the dog, however, only 11.8% owners were keeping dog for safety at their home. Labradorwas the most preferred breed among the responder (34.4%), followed by Pomeranian (11.8%). Most of the owners(81.7%) maintained single dog and about 50.5% owners did not breed the female, whereas 24.7% maintained thefemale without breeding after a single whelping. The awareness about use of hormones in controlling estrus andtermination of pregnancy was negligible, only 3.2% owners have used hormones as contraceptive. Most of thempreferred to consult veterinarian at Government hospitals than private veterinary dispensary. Although, majority ofresponders used disinfectant for cleaning the area used by their pet, around 15% responders did not use any disinfectant.Thus, more preference towards single or no whelping until middle to advance age and lack of awareness on regularbreeding and proper use of antiseptic and disinfectant for cleaning of pet cages or houses could be the major riskfactors for development of CEH-pyometra in the bitch.
Keywords: Socio-economic; Dog; Management; Breeding; Pyometra